PROSES PENAMAAN DESA DI KABUPATEN SLEMAN: TINJAUAN SEMANTIS - Nusarini N (LITERASI: Indonesian Journal of Humanities, 2014)
This article aims to describe the background of village naming and linguistic rules of village names in Sleman. The research was conducted through three stages: the data collection, the analyzing of data, and the exposition of analysis results. The village names taken as the sample is located in Cangkringan, Pakem, Turi, and Gamping. The results reveal that the background of the naming of villages can be classified based on the process of naming village based on the etymology of the elements of nature such as mountains, plants, forests, and water; elements of the verb; and non-nature etymology, and the process of naming the village by village history. The aspects of language used in naming the village in Sleman Yogyakarta are the names of the villages having polymorfemic word form. In the form of polymorfemic words there is an element consisting of two constituent monomorfem and consists of one constituent monomorfem and one constituent polymorfem. Keywords: Toponymy, village names, polymorfem